Percepciones en conflicto: las imágenes públicas del Opus Dei en Estados Unidos durante los años Cincuenta / Conflicting Perceptions: The Public Images of Opus Dei in the United States during the 1950s - Federico M. Requena (Studia et Documenta, 2025)
The public perceptions of Opus Dei in the United States from its arrival in 1949 until the summer of 1957 are analyzed. The starting point are eighty news articles and articles published during this period, both in Catholic and non-Catholic media. In addition, special attention is paid to the documentation that allows us to reconstruct, as far as possible, the contexts in which these reports appeared, as well as the reactions they provoked. This journey allows us to see a multiplicity of perceptions, conflicting images, which ranged from adequate representations of the nature and purpose of Opus Dei, through distorted images from a juridical and theological perspective, to purely political readings of the institution, linked to the Spanish political situation. The study attempts to identify a possible interaction between the institutional and juridical dimensions, linked to Opus Dei’s status as a secular institute at the time, and these public perceptions.